High level expression of a gene coding for pectate lyase in Bacillus subtilis 168 - Bac, Vo Hoai; Thu Hang, Do Thi; Tai, Le Trong; Truong, Le Van (Academia Journal of Biology, 2013)
Pectate lyase degrade polygalacturonate of plant cell wall productes oligogalacturonates. In recent years, pectate lyase has attracted the considerable research interest because of their potential industrial application, for instance in the textile industry, paper making. Gene pel coding for pectate lyase from Bacillus subtilis VBS11 was subcloned and fused with α-amylase promoter from B. amyloliquefaciens (BApro). This construct was ligated into vector pMSE3 and transformated into the host strain BS168 for over expression under control of BApro promoter from B. amyloliquefaciens. rPel was producted in high level of 88,6 U/ml in Belisky minimal medium.